Low molecular weight hyaluronan-pulsed human dendritic cells showed increased migration capacity and induced resistance to tumor chemoattraction. - Manglio Rizzo; Juan Bayo; Flavia Piccioni; Mariana Malvicini; Esteban Fiore; Estanislao Peixoto; Mariana G García; Jorge B Aquino; Ariel Gonzalez Campaña; Gustavo Podestá; Marcelo Terres; Oscar Andriani; et al. (PLoS ONE, 2014)
We have shown that ex vivo pre-conditioning of bone marrow-derived dendritic cells (DC) with low molecular weight hyaluronan (LMW HA) induces antitumor immunity against colorectal carcinoma (CRC) in mice. In the present study we investigated the effects of LMW HA priming on human-tumor-pulsed monocytes-derived dendritic cells (DC/TL) obtained from healthy donors and patients with CRC. LMW HA treatment resulted in an improved maturation state of DC/TL and an enhanced mixed leucocyte reaction activity in vivo. Importantly, pre-conditioning of DC/TL with LMW HA increased their ability to migrate and reduced their attraction to human tumor derived supernatants. These effects were associated with increased CCR7 expression levels in DC. Indeed, a significant increase in migratory response toward CCL21 was observed in LMW HA primed tumor-pulsed monocyte-derived dendritic cells (DC/TL/LMW HA) when compared to LWM HA untreated cells (DC/TL). Moreover, LMW HA priming modulated other mechanisms implicated in DC migration toward lymph nodes such as the metalloproteinase activity. Furthermore, it also resulted in a significant reduction in DC migratory capacity toward tumor supernatant and IL8 in vitro. Consistently, LMW HA dramatically enhanced in vivo DC recruitment to tumor-regional lymph nodes and reduced DC migration toward tumor tissue. This study shows that LMW HA--a poorly immunogenic molecule--represents a promising candidate to improve human DC maturation protocols in the context of DC-based vaccines development, due to its ability to enhance their immunogenic properties as well as their migratory capacity toward lymph nodes instead of tumors.